Biology and Management of Navel Orangeworm (Lepidoptera: Pyralidae) in California. (25th December 2020) - Wilson, Houston; Burks, Charles S; Reger, Joshua E; Wenger, Jacob A
Abstract: Navel orangeworm, Amyelois transitella (Walker), is a primary pest of almonds, pistachios, and walnuts in California. These specialty tree nut crops are widely planted across the state and account for a significant share of total agricultural revenue, with 1.7 million combined acres generating a total farm-gate value of $8.9 billion. Larvae of A. transitella cause direct damage to the nut, burrowing into the kernel and contaminating it with frass and webbing, while adults are able to introduce fungi during oviposition that produce aflatoxin, a known human carcinogen that is heavily regulated both domestically and in key foreign markets. As such, there is little tolerance for A. transitella infestation, and most operations aim for <2% crop damage from this pest. Currently, integrated management of A. transitella involves a combination of orchard sanitation, well-timed insecticide sprays, timely harvest, and, most recently, mating disruption. Additional novel tools, such as sterile insect technique, are currently being explored. This species has a strong dispersal capacity, and given the extensive, and many times contiguous, acreage of tree nuts in California, long-term management will require the development of an effective area-wide management strategy. Tools, tactics, and conditions are in an ongoing state of change, and therefore pest management for this economically important species is a work in progress. Here, we discuss the biology, seasonal phenology, monitoring, and management of A. transitella across almonds, pistachios, and walnuts.